2021
DOI: 10.1001/jamaoncol.2021.1799
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Convalescent Plasma Therapy With Survival in Patients With Hematologic Cancers and COVID-19

Abstract: IMPORTANCE COVID-19 is a life-threatening illness for many patients. Prior studies have established hematologic cancers as a risk factor associated with particularly poor outcomes from COVID-19. To our knowledge, no studies have established a beneficial role for anti-COVID-19 interventions in this at-risk population. Convalescent plasma therapy may benefit immunocompromised individuals with COVID-19, including those with hematologic cancers.OBJECTIVE To evaluate the association of convalescent plasma treatment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 162 publications
(115 citation statements)
references
References 43 publications
8
99
0
2
Order By: Relevance
“…These patients have impaired seroconversion due to COVID-19 infection and COVID-19 vaccination, and the biologic rationale for using viable antibodies from a recovered donor is strong [70]. Thompson and et al [71] conducted a retrospective cohort study on propensity score-matched patients with hematologic malignancies and COVID-19 from the CCC-19 registry. The authors found that the use of convalescent plasma was associated with a lower 30-day mortality (HR: 0.60, 95% CI: 0.29-0.92) and lower mortality in those admitted to an intensive care unit (0.4, 95% CI: 0.2-0.8) or receiving mechanical ventilation (0.32, 95% CI: 0.14-0.72).…”
Section: Covid-19 Therapeutics In Patients With Hematologic Malignanciesmentioning
confidence: 99%
“…These patients have impaired seroconversion due to COVID-19 infection and COVID-19 vaccination, and the biologic rationale for using viable antibodies from a recovered donor is strong [70]. Thompson and et al [71] conducted a retrospective cohort study on propensity score-matched patients with hematologic malignancies and COVID-19 from the CCC-19 registry. The authors found that the use of convalescent plasma was associated with a lower 30-day mortality (HR: 0.60, 95% CI: 0.29-0.92) and lower mortality in those admitted to an intensive care unit (0.4, 95% CI: 0.2-0.8) or receiving mechanical ventilation (0.32, 95% CI: 0.14-0.72).…”
Section: Covid-19 Therapeutics In Patients With Hematologic Malignanciesmentioning
confidence: 99%
“…There were 47 studies 16‐62 fulfilled the inclusion criteria and were used for the systematic review and meta‐analysis (Figure 1). Of 47 included studies, 21 were clinical trials 16‐33,60‐62 and 26 were observational studies 34‐59 . Among clinical trials, there were 18 studies published in peer‐reviewed journals 16‐33 while the other three were preprints 60‐62 .…”
Section: Resultsmentioning
confidence: 99%
“…All studies provided complete outcome data and were clear from reporting bias (Table S5). For observational studies, there were ten studies conducted in the USA 35,42,45,50,52,[54][55][56][57]59 ; three in China 36,37,43 ; three in Poland 40,48,58 ; three in India 41,47,51 ; two in Turkey 34,39 ; and one each in United Arab Emirates, 38 Austria, 44 Brazil, 46 Qatar 49 and Argentina. 53 Almost of observational studies included patients with severe or critical COVID-19 disease (Table 2).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations